2014
DOI: 10.1037/a0036048
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for cultural dialects in vocal emotion expression: Acoustic classification within and across five nations.

Abstract: The possibility of cultural differences in the fundamental acoustic patterns used to express emotion through the voice is an unanswered question central to the larger debate about the universality versus cultural specificity of emotion. This study used emotionally inflected standard-content speech segments expressing 11 emotions produced by 100 professional actors from 5 English-speaking cultures. Machine learning simulations were employed to classify expressions based on their acoustic features, using conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 22 publications
8
43
0
Order By: Relevance
“…Altrov 2013, Bryant and Barrett 2008, and Jürgens et al 2013). According to Laukka et al (2014) as well as to Scherer et al (2011) the universality of emotions is supported by the fact that if a listening task requires the classification of emotions of any culture into predetermined categories, recognition accuracy is b etter than chance probability. However, research has revealed that emotion expressions are better identified by members of one's own culture (so-called in-group advantage).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Altrov 2013, Bryant and Barrett 2008, and Jürgens et al 2013). According to Laukka et al (2014) as well as to Scherer et al (2011) the universality of emotions is supported by the fact that if a listening task requires the classification of emotions of any culture into predetermined categories, recognition accuracy is b etter than chance probability. However, research has revealed that emotion expressions are better identified by members of one's own culture (so-called in-group advantage).…”
Section: Introductionmentioning
confidence: 99%
“…However, research has revealed that emotion expressions are better identified by members of one's own culture (so-called in-group advantage). A poorer performance in identifying the emotion expressions of other cultures may be due to cultural differences in emotion expression (Elfenbein 2013, andLaukka et al 2014). True, most proof of the universality of emotion recognition has been obtained from cross-cultural studies of the face, while cross-cultural studies of the identification of vocal emotions in speech are much rarer (see Uskul 2014, andPell et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study with machine learning simulation aims to make the first attempt to isolate the impact of physical properties of auditory stimuli from that of cultural norms that affect the perceptual-acoustic classification of vocal expressions [34]. In this study, acoustic features were extracted from short utterances expressing 11 typical emotions (anger, contempt, fear, happiness, interest, neutral, sexual lust, pride, relief, sadness and shame), produced by 100 professional speakers from 5 English-speaking cultures (Australia, India, Kenya, Singapore and USA).…”
Section: Language Proficiency and Cultural Immersion Impact Language Usementioning
confidence: 99%
“… ii When universality is assumed, this modulation is proposed to occur via culturally set rules for what (and when) inborn expressions are appropriate to display, i.e., display rules [54], or via culturally acquired accents that modulate the form of innate facial actions [55] and vocalizations [56]. …”
mentioning
confidence: 99%